(3JMhd GdbQGQ GdEOGQjs - (3eMeO YHO Gddg MehO(B, (3GdOjdejs ((3YeGf(B;(3OGQ GdKbGaI ddfTQ(B:s (3GdOGQ GdYdejI GdOhdjI ddfTQ hGdJhRjY(B,s, 2001)
(3eGgjI JMhd GdJUQa GdbGfhfj aj fWGb GdbGfhf GdNGU(B-(3TQhW JMhd GdbQGQ GdEOGQj(B-(3ELQGAGJ GdJMhd hBKGQg(B-(3JejjR GdJMhd Yf ZjQg ef GdCacGQ GdebGQfIs
(3HHdjhZQGajG(B: (3U(B.173s
Keywords: (3GdbGfhf GdGOGQjs; (3GdbQGQGJ GdEOGQjIs